Comprehensive identification, characterization and expression analyses of the class III POD gene family in water lily (Nymphaea colorata) - Khan, Wasi Ullah; Khan, Latif Ullah; Khan, Noor Muhammad; Zhang, Ji; Wenquan, Wang; Chen, Fei (Frontiers in Plant Science, 2025)
Class III peroxidases are plant-specific glycoproteins and widely distributed among plant species, that play a crucial role in plant resistance to different stresses, such as salt, heat, cold and metal toxicity. The present study is the first comprehensive and systematic report to characterize the NcPOD gene family in water lily (Nymphaea colorata). In this study, 94 NcPOD genes in water lily were identified, each possessing a conserved POD domain, which are dispersed unevenly across the genome. Through comparative maximum-likelihood phylogenetic analysis, these genes were categorized into 10 groups, along with two other species, Arabidopsis thaliana and Nymphaea thermarum. Notably, the largest group, group-c, comprised 32 distinct types of NcPOD proteins. These genes exhibited uneven distribution on 11 of the 14 chromosomes of water lily. Exon-intron and motif analyses exhibited the structural and functional diversity among the sub-groups. The Examination of duplication patterns suggests that tandem duplication has contributed to the expansion of NcPOD genes. The analysis of promoter cis-acting elements indicated the presence of regulatory elements associated with various responses such as ABA, MeJA, light responsiveness, anaerobic conditions, and drought inducibility. Finally, the RT-qPCR based expression and enzymes activity of ten NcPOD genes depicted the dynamically differential response to NaCl, heat, cold, and heavy metals (CuSO4 and CdCl2) stresses. These findings provide valuable insights for future exploration of NcPOD functions in water lily growth and stress tolerance, laying a foundation for further comparative genomics and functional studies of this important class of antioxidant genes.